Trauma and Resilience in Exile and Womanhood in Alyan’s Salt Houses and Nayeri’s Refuge - Kholoud Al-Ghamdi (LPPM Universitas Advent Indonesia, 2026)
Exile reshapes the inner life of families, leaving traces that outlast borders. This study traces how Hala Alyan’s Salt Houses and Dina Nayeri’s Refuge portray trauma, memory, and the quiet forms of resistance that sustain displaced identities. The research highlights the importance of understanding exile as a psychological and cultural inheritance rather than a single historical rupture. It addresses a clear gap in existing scholarship, since the two novelists are rarely examined together despite their shared focus on intergenerational loss and narrative reconstruction. Using a comparative hermeneutic method grounded in close reading, the study analyzes how both writers transform fragmented memories into creative acts of survival. The findings show that Alyan emphasizes communal and matrilineal remembrance, while Nayeri foregrounds linguistic estrangement and personal reclamation, revealing storytelling as an ethical mode of agency. These insights offer implications for trauma studies and Middle Eastern women’s literature by demonstrating how narrative reworks inherited pain into renewed belonging. The study recommends further cross-cultural comparisons of refugee narratives and suggests that the analytic process used here can be replicated in other diasporic contexts. Future research may extend this framework to digital memoirs and emerging hybrid narrative forms.